Extra Losses in Imperfect Closed Grids - Survilo, Josifs; Biela, Edite (Electrical, Control and Communication Engineering, 2011)
Closed grids consist of two-terminal power lines or/and of rings (loops). In non-uniform two-terminal lines, equalizing and circulating currents appear, in rings - circulating current. These currents cause extra power losses. Those losses are equal to the product of summary resistance and squared said extra currents and are independent of the direction of said currents. Equalizing current causes considerable losses by phase discrepancy of terminal voltages even when voltage magnitudes are equal. Equalizing current losses do not exceed 1/4 of load losses when terminal voltage difference is equal to maximum load voltage loss. The degree of non-uniformity of inhomogeneous rings can be estimated by inhomogeneous factor. The increased reliability and higher electricity quality in distribution grids can be attained by use of uniform or ameliorated ringed grids but the reservation can be implemented by controllable links between adjacent rings.